2021
DOI: 10.3390/coatings11091120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Pretreatment of Titanium Substrates on Properties of Electrophoretically Deposited Biopolymer Chitosan/Eudragit E 100 Coatings

Abstract: The preparation of the metal surface before coating application is fundamental in determining the properties of the coatings, particularly the roughness, adhesion, and corrosion resistance. In this work, chitosan/Eudragit E 100 (chit/EE100) were fabricated by electrophoretic deposition (EPD) and both their microstructure and properties were investigated. The present research is aimed at characterizing the effects of the surface pretreatment of titanium substrate, applied deposition voltage, and time on physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 78 publications
(91 reference statements)
2
19
0
Order By: Relevance
“…The distance between the electrodes was set at 10 mm. In Procedure A, according to previous studies [ 15 ], the anodization voltage and time were adjusted to 20 V and 20 min, respectively. After oxidation, the samples were washed thoroughly with distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The distance between the electrodes was set at 10 mm. In Procedure A, according to previous studies [ 15 ], the anodization voltage and time were adjusted to 20 V and 20 min, respectively. After oxidation, the samples were washed thoroughly with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…There have been some papers in the last few years describing corrosion parameters of different coatings deposited or layers created on titanium [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and its alloys: Ti6Al4V [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], Ti13Nb13Zr [ 14 , 24 , 25 , 26 , 27 ]. The coatings were designed and produced particularly to enhance corrosion resistance [ 1 , 4 , 6 , 7 , 8 , 9 , 11 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 24 ] or the corrosion characteristics were determined only to verify whether and to what extent the applied coating may affect the degradation process [ 5 , 10 , 12 , 13 , 14 , 15 , 20 , 25 ]. The main difference between coated materials was the presence or the absence of an artificial titanium oxide layer created by oxidation in different conditions [ …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been shown that a pre-treatment of a substrate surface has a positive effect on the morphology and properties of electrophoretically deposited biopolymer coatings. 7,8 Experimental studies on material surface coatings show that, for example, the contact welding method improves the properties of coatings and further makes it possible to modify them, while ion nitriding in a glow charge with deposition of protective coatings increases adhesion properties and corrosion resistance. 9,10 However, finding conditions to achieve optimal mechanical characteristics of a coating requires a great amount of efforts both from technological and fundamental aspects for studying the features of structure and property formation.…”
Section: Introductionmentioning
confidence: 99%